The test of availability of rights against the principle of inalienability in the new labor process - Gerónimo de la Cruz, Jaime (2020)
The oralization settlement in the labor process has implied a different dynamic from that previously had. But this has not been the only change in the labor reform. Therefore, the new procedural system has incorporated diversity legal process forms of settlement agreements. Thus, the employer or employee can exercise their right of action to resort to other mechanisms that resolve disagreement in the employment relationship. This new legislative method has brought us to establish two antagonistic positions: on the one hand, some who support the viability of applying the availability test based on private autonomy and the initiative of part in the process; and on the other hand, those who argue, under the principle of inalienability, the protective role that the judge should have against these processes.